Acupoint herbal patching for bronchitis: A systematic review and meta-analysis. Issue 26 (30th June 2022) - Jun, Ji Hee; Kim, Kyeong Han; Song, Eunhye; Ang, Lin; Park, Sunju
Abstract : Background: Acupoint herbal patching (AHP) has long been used to treat patients with bronchitis in East Asia. This review assessed the efficacy and safety of AHP as a treatment for bronchitis. Methods: We performed a literature search using the 9 databases and included randomized controlled trials (RCTs) or quasi-RCTs that used AHP for bronchitis. The methodological quality of each RCT was assessed using the Cochrane Handbook version 5.3, the risk of bias tool, and Grading of Recommendations Assessment, Development and Evaluation (GRADE). Results: Seven RCTs were included based on the inclusion criteria. All RCTs were published in China and had a high risk of bias. Three RCTs compared AHP with conventional drug therapy for the treatment of bronchitis. The meta-analysis also showed a significant improvement in treatment effectiveness (relative risk [RR] 1.28, 95% confidence interval [CI] 1.15, 1.42; P < .00001; I 2 = 0%). Two RCTs investigated AHP combined with conventional drug therapy versus conventional drug therapy. The meta-analysis showed that AHP was significantly more effective than conventional therapy in terms of treatment effective rate (RR 1.16, 95% CI 1.03, 1.29; P = .01; I 2 = 0%). Three RCTs reported adverse events, and none reported severe adverse events. Conclusions: AHP appears to be more effective than conventional drug therapy alone or a placebo. Furthermore, the AHP appears to be a safe treatment option. However, due to the small number of included trials and their poor methodological quality, future studies should include larger sample sizes and well-designed RCTs. Trial registration number: PROSPERO: CRD 42018110380.